2019
DOI: 10.3389/fendo.2019.00224
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanisms and Signaling Pathways Involved in Sertoli Cell Proliferation

Abstract: Sertoli cells are somatic cells present in seminiferous tubules which have essential roles in regulating spermatogenesis. Considering that each Sertoli cell is able to support a limited number of germ cells, the final number of Sertoli cells reached during the proliferative period determines sperm production capacity. Only immature Sertoli cells, which have not established the blood-testis barrier, proliferate. A number of hormonal cues regulate Sertoli cell proliferation. Among them, FSH, the insulin family o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
138
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 172 publications
(148 citation statements)
references
References 318 publications
(315 reference statements)
7
138
0
3
Order By: Relevance
“…20,23,36 In this study, the results demonstrated that our obtained protein could promote the F I G U R E 3 Mitogenic and proliferation activity analysis of different concentrations of rhMYDGF on HCAECs in vitro. 20,23,36 In this study, the results demonstrated that our obtained protein could promote the F I G U R E 3 Mitogenic and proliferation activity analysis of different concentrations of rhMYDGF on HCAECs in vitro.…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…20,23,36 In this study, the results demonstrated that our obtained protein could promote the F I G U R E 3 Mitogenic and proliferation activity analysis of different concentrations of rhMYDGF on HCAECs in vitro. 20,23,36 In this study, the results demonstrated that our obtained protein could promote the F I G U R E 3 Mitogenic and proliferation activity analysis of different concentrations of rhMYDGF on HCAECs in vitro.…”
Section: Discussionsupporting
confidence: 51%
“…It is well known that MAPK/STAT3 and PI3K signalling pathways are important for cell growth and survival. 20,23,24 Therefore, we aimed to determine whether the rhMYDGF-mediated HCAEC proliferation is associated with MAPK/STAT3 or PI3K signalling pathway. Notably, consistent with previous report, when HCAECs were treated with 100 ng/mL of rhMYDGF protein in vitro for 0, 5 and 15 minutes, respectively, the phosphorylation of MAPK1/3 and STAT3 on S727 was significantly enhanced with the time extending, while that did not occur at vehicle treatment ( Figure S6), suggesting the effect of rhMYDGF on HCAEC mitosis was closely related to the activation of MAPK1/3/STAT3 (S727), whereas rhMYDGF did not increase the phosphorylation of STAT3 on Y705 ( Figure 4A and 4), which is required for STAT3 dimerization and nuclear translocation.…”
Section: Mapk1/3/stat3 Cyclin D1 and Pi3k/akt Signal Activation Inmentioning
confidence: 99%
See 1 more Smart Citation
“…,30 However, opposite results on plasma IB and AMH levels during CC cannot be excluded, as T has the opposite effect on IB and AMH secretion 29,31. Meanwhile, the rise of E2 levels after CC treatment should be considered for their facilitating role in SCs proliferation 32. In contrast, during CC treatment, Overall, our data may point the possibility of damage to SCs in obese dysmetabolic men, thus supporting the hypothesis of a reduced number of SCs in obese compared with normal weight subjects 33.…”
supporting
confidence: 64%
“…However, opposite results on plasma IB and AMH levels during CC cannot be excluded, as T has the opposite effect on IB and AMH secretion . Meanwhile, the rise of E2 levels after CC treatment should be considered for their facilitating role in SCs proliferation . In contrast, during CC treatment, a parallel rise in endogenous levels of E2 and T (both about 40%) was found without altering the T/E2 ratio (pretreatment: O.16 ± 0.05 and post‐treatment 0.15 ± 0.05, P = .374) which supports the lack of damage of testicular steroidogenesis in our patients likely due to a dysfunctional hypothalamic‐pituitary‐testis axis …”
Section: Discussionmentioning
confidence: 82%